2020
DOI: 10.1136/bmjopen-2020-038351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active referral combined with a small financial incentive on smoking cessation: study protocol for a cluster randomised controlled trial

Abstract: IntroductionEvidence-based smoking cessation treatments are effective but underutilised, accentuating the need for novel approaches to increase use. This trial investigates the effects of active referral combined with a financial incentive to use smoking cessation services on smoking abstinence among community smokers.Methods and analysisThis ongoing study is a two-arm, assessor-blinded, pragmatic, cluster randomised controlled trial with follow‐ups at 1, 2, 3 and 6 months after randomisation. We aim to enrol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 10 , 11 , 17 , 23 , 24 The trial protocol approved by the Institutional Review Board (IRB) of the University of Hong Kong/Hospital Authority Hong Kong West Cluster (UW18–318) has been registered with ClinicalTrials.gov ( NCT03565796 ) and published elsewhere. 25 Consolidated Standards of Reporting Trials (CONSORT) reporting guideline was followed.…”
Section: Methodsmentioning
confidence: 99%
“… 10 , 11 , 17 , 23 , 24 The trial protocol approved by the Institutional Review Board (IRB) of the University of Hong Kong/Hospital Authority Hong Kong West Cluster (UW18–318) has been registered with ClinicalTrials.gov ( NCT03565796 ) and published elsewhere. 25 Consolidated Standards of Reporting Trials (CONSORT) reporting guideline was followed.…”
Section: Methodsmentioning
confidence: 99%
“…Survey 2 was a telephone survey conducted from 7 May to 30 June 2020, including subjects who formerly participated in the 'Quit to Win' project for smokers in 2018 and 2019 (organized annually by the Hong Kong Council on Smoking and Health in collaboration with us). The 'Quit to Win' project has been reported elsewhere 32,33 . Among the 968 people invited, 769 (79.4%) agreed to participate.…”
Section: Data Collectionmentioning
confidence: 99%
“…Our previous trial showed active referral plus a small monetary incentive was effective in increasing smoking cessation service use and abstinence [ 36 ]. To promote smoking cessation service use, participants who are verbally committed to using any smoking cessation services within 2 months will receive a pre-paid monetary incentive (HK$100, ≈ US$ 12.8) by post.…”
Section: Methodsmentioning
confidence: 99%